Corporate Social Responsibility in Indonesian Banking: The Role of Intellectual Capital and Board Diversity - Dwita Indah Bestari; Bima Cinintya Pratama; Azmi Fitriati; Rina Mudjiyanti (ITB AAS INDONESIA, 2023)
The purpose of this study was to examine the effect of intellectual capital on Corporate Social Responsibility Disclosures and to consider the effect of the educational background of the directors and the gender of the female board of directors on the disclosure of corporate social responsibility. The population used in this study are bank companies registered with the Financial Services Authority (OJK) with a sample of 41 bank companies for the 2017-2021 period. This research uses panel data regression model analysis. The analytical technique used in this research is the descriptive statistical test, preliminary test (Breusch-Pagan, likelihood test, Hausman test), diagnostic test (heteroscedasticity test and autocorrelation test), and hypothesis testing. Based on the results of the three preliminary tests in determining the panel data regression model, this study will use a random effects model to examine the relationship between variables. The results of this study indicate that Intellectual Capital has a positive effect on Corporate Social Responsibility Disclosure, a company can work optimally with good resources and strong customer relationships, to increase CSR disclosure. The educational background variable of directors has a negative effect on Corporate Social Responsibility Disclosure, the ability of directors is not only measured by their formal education which is hard skills, but also by soft skills in running a business. The female board of directors' gender variable has a positive effect on Corporate Social Responsibility Disclosure. The existence of women as company directors can make a real contribution to increasing the amount of CSR disclosure. Therefore, there is no empirical evidence that the educational background of the board of directors and the gender of the board of directors can strengthen intellectual capital on the disclosure of corporate social responsibility.